Prognostic value of the periodontal risk assessment in patients with aggressive periodontitis - Bäumer, Amelie; Pritsch, Maria; Cosgarea, Raluca; Sayed, Nihad el; Kim, Ti-Sun; Eickholz, Peter; Pretzl, Bernadette (Journal of clinical periodontology, 2012)
Objectives Aim of the study was to evaluate the predictive value of the modified periodontal risk assessment (PRA) in patients with aggressive periodontitis (AgP) for the first time. Material and Methods A total of 86 Patients with AgP were re-examined 5-17 years after active periodontal treatment. Risk profile according to the modified PRA was assigned and regularity of maintenance monitored. Tooth loss, bone loss and recurrence of periodontitis were analysed in association with gender, diagnosis, compliance and risk profile using uni- and multivariate parametric regression and Cox proportional hazards models. Results A total of 14 patients showed a localized AgP, 60 a high-risk-profile and 19 were compliant with the proposed maintenance-interval. Of 2202 teeth 98 were lost. Multivariate analysis could not assign a statistically significant impact to risk-profile. By excluding Interleukin-1 composite genotype from the modified PRA a significant influence (p = 0.003, HR 2.74) was detected. The impact of compliance was shown to be nearly significant (p = 0.059, HR 2.0). In patients with generalized AgP a tendency for increased tooth loss was found. Conclusion The prognostic value of the modified PRA could not be confirmed in patients with AgP. However, exclusion of Interleukin-1 composite genotype led to a model with significant influence on tooth loss.